Impact of IDH Mutations on DNA Methylation of Acute Myeloid Leukemia Related Genes: A Review Article - M. Bayram, Duha; M. Lafta, Fadhel; F. Matti, Bassam (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Acute myeloid leukemia is one of the deadliest hematologic malignancies that is marked by genetic alterations, abnormal cellular functions, and proliferation. Mutations in isocitrate dehydrogenase genes, particularly isocitrate dehydrogenase gene 1 and isocitrate dehydrogenase gene 2, have emerged as recurrent genetic abnormalities in acute myeloid leukemia. These mutations lead to abnormal enzymatic activity, accumulating 2-hydroxyglutarate, which disrupts normal cellular processes including DNA methylation. Objectives: This review article explores recent findings related to the implication of isocitrate dehydrogenase gene mutations on the acute myeloid leukemia epimethylome and provides evidence of the relationship between these mutations and the pathogenesis, prognosis, and treatment of acute myeloid leukemia. Methods: A comprehensive literature search was conducted to identify relevant studies investigating the impact of isocitrate dehydrogenase mutations on altered DNA methylation patterns of acute myeloid leukemia-related genes. The selected studies were reviewed and analyzed to highlight the significance of their findings. Results: The review highlights that isocitrate dehydrogenase gene mutations in acute myeloid leukemia are associated with widespread changes in DNA methylation patterns. These alterations primarily affect DNA methylation of acute myeloid leukemia-associated genes, including DNA methyltransferases and ten-eleven translocation proteins. Such epigenetic dysregulation in the DNA methylation modifying genes contributes to global DNA hypermethylation and specific gene hypomethylation leading to abnormal cellular functions and the development of acute myeloid leukemia. Conclusion: The findings of this review support the significant impact of isocitrate dehydrogenase gene mutations on DNA methylation of acute myeloid leukemia-related genes. Understanding the interplay between isocitrate dehydrogenase gene mutations and DNA methylation dysregulation provides insights into acute myeloid leukemia pathogenicity and may have implications for prognostication and targeted therapies.